Piero della Francesca the Arezzo Frescoes - Piero della Francesca 1416-1492 (Rizzoli art series, 1992)
In this book, Perry Brooks, an authority on Italian Renaissance painting who has taught at Columbia University, introduces the subtleties of Piero's frescoes for the general reader and solves a conundrum of their narrative organization that has long puzzled specialists.